The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1097/cce.0000000000000692
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps and Delayed Cerebral Ischemia in Aneurysmal Subarachnoid Hemorrhage

Abstract: IMPORTANCE: Myeloperoxidase (MPO)-DNA complexes, biomarkers of neutrophil extracellular traps (NETs), have been associated with arterial and venous thrombosis. Their role in aneurysmal subarachnoid hemorrhage (aSAH) is unknown. OBJECTIVES: To assess whether serum MPO-DNA complexes are present in patients with aSAH and whether they are associated with delayed cerebral ischemia (DCI). DESIGN, SETTING, AND PARTICIPANTS: Post-hoc analysis of a prospective, observational single-center study, with de novo serum … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…We conducted a post-hoc analysis with de novo investigation of myeloperoxidase (MPO)-DNA complexes, a biomarker of released NETs in circulation. Effectively, for the first time, it was demonstrated that MPO-DNA complex levels were significantly associated with DCI (8,9). These observations in context with the current literature incited us to further explore NET and NET-related biomarkers in the same cohort that are complementary to HMGB1 and MPO-DNA complexes.…”
Section: Introductionmentioning
confidence: 71%
“…We conducted a post-hoc analysis with de novo investigation of myeloperoxidase (MPO)-DNA complexes, a biomarker of released NETs in circulation. Effectively, for the first time, it was demonstrated that MPO-DNA complex levels were significantly associated with DCI (8,9). These observations in context with the current literature incited us to further explore NET and NET-related biomarkers in the same cohort that are complementary to HMGB1 and MPO-DNA complexes.…”
Section: Introductionmentioning
confidence: 71%
“…Apart from that, Witsch et al showed that high concentrations of MPO-DNA complexes were present in all patients with aneurysmal SAH on admission regardless of the development of delayed cerebral ischemia (DCI) or clinical vasospasm. Additionally, increased NLR as a marker of post-SAH inflammation was consistently linked in different studies with DCI [ 42 ]. Finally, in autopsies of patients who died of spontaneous ICH, Puy et al found that the total number of neutrophils was increased in the area of the hematoma compared with the contralateral sections in control groups, in which no neutrophils were observed within the tissue.…”
Section: Resultsmentioning
confidence: 99%
“…On another note, in SAH patients, MPO-DNA levels seemed to decrease on day 4 in patients with DCI and patients with clinical vasospasm [ 42 ]. This finding also supports the abovementioned idea that more research is needed to assess the potential use of NETs as a potent biomarker to predict time of onset.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations